Penerapan Konseling Kelompok dengan Teknik Assertive Adaptive untuk Mengatasi Penyesuaian Diri - Azizah Pebrianti; Abdur Razzaq; Lena Marianti (Journal of Society Counseling, 2024)
Basically, adjustment involves individuals and their environment, this is also the case with inmates, this is because inmates who have just entered are required to be able to adapt to environmental conditions, individuals, and the rules that apply in prison. According to Picken, new inmates experience higher levels of stress. Therefore, to help solve adjustment problems for inmates in prison, researchers applied assertive adaptive techniques with group counseling services. Therefore, the researcher chose the title "Application of Group Counseling with Assertive Adaptive Techniques to Overcome Self-Adjustment". This research was carried out at the Class IIA Palembang Women's Correctional Institution (Lapas Perempuan). The aim of this research is to find out the description of the application of group counseling using assertive adaptive techniques and to find out the description of the self-adjustment of female inmates after implementing group counseling with assertive adaptive techniques. Researchers use qualitative methods with data collection techniques such as observation, interviews and documentation, and use data analysis techniques such as data reduction, namely selecting data that is not useful then presenting the data that has been collected and drawing conclusions. The results of this research show that group counseling using the assertive adaptive technique was successfully applied to the inmates and after implementing group counseling with the assertive adaptive technique, some of the inmates were able to slowly interact and adapt themselves to new people. However, it is true that some of the inmates only follow and close themselves off from new people and are not yet able to adapt.